2020
DOI: 10.1089/cren.2020.0050
|View full text |Cite
|
Sign up to set email alerts
|

Exuberant Malakoplakia of the Prostate Presenting as Prostatic Abscesses in an Immunocompromised Patient

Abstract: Background: Malakoplakia is a rare benign lesion, usually associated with deficient intralysosomal degradation of microorganisms, more commonly, Escherichia coli. Malakoplakia occurs in various organ systems, the most frequently affected site being the urinary bladder. We report a rare case of isolated extensive malakoplakia involving the prostate, diagnosed on transurethral resection performed for radiologically suspected prostatic abscesses. Case Presentation: A 61-year-old African American male presented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In such a case, if the periprostatic fascia and envelope are cut and accidentally enter the prostate gland, a portion of the fascia and envelope disappears from the specimen, leaving cancerous tissue inside the prostate on the ink-stained margins, i.e., false positive ( 14 ). Men with post-prostate cancer resection specimens suggestive of PSM have a higher chance of experiencing clinical biochemical recurrence ( 15 ). A large multi-institutional study showed a 3.7-fold association between PSM and the risk of biochemical recurrence in nearly 6,000 men treated with prostate cancer resection.…”
Section: Introductionmentioning
confidence: 99%
“…In such a case, if the periprostatic fascia and envelope are cut and accidentally enter the prostate gland, a portion of the fascia and envelope disappears from the specimen, leaving cancerous tissue inside the prostate on the ink-stained margins, i.e., false positive ( 14 ). Men with post-prostate cancer resection specimens suggestive of PSM have a higher chance of experiencing clinical biochemical recurrence ( 15 ). A large multi-institutional study showed a 3.7-fold association between PSM and the risk of biochemical recurrence in nearly 6,000 men treated with prostate cancer resection.…”
Section: Introductionmentioning
confidence: 99%
“…In such a case, if the periprostatic fascia and envelope are cut and accidentally enter the prostate gland, a portion of the fascia and envelope disappears from the specimen, leaving cancerous tissue inside the prostate on the inkstained margins, i.e., false positive (14). Men with post-prostate cancer resection specimens suggestive of PSM have a higher chance of experiencing clinical biochemical recurrence (15). A large multiinstitutional study showed a 3.7-fold association between PSM and the risk of biochemical recurrence in nearly 6,000 men treated with prostate cancer resection.…”
Section: Introductionmentioning
confidence: 99%